Answer:
see explanation
Step-by-step explanation:
given the 2 equations
y = x² - 2x - 19 → (1)
y + 4x = 5 → (2)
substitute y = x² - 2x - 19 into (2)
x² - 2x - 19 + 4x = 5 ( subtract 5 from both sides )
x² + 2x - 24 = 0 ← in standard form
(x + 6)(x - 4) = 0 ← in factored form
equate each factor to zero and solve for x
x + 6 = 0 ⇒ x = - 6
x - 4 = 0 ⇒ x = 4
substitute each value of x into (1) for corresponding y- coordinate
x = - 6 : y = (- 6)² - 2(- 6) - 19 = 36 + 12 - 19 = 29 ⇒ (- 6, 29)
x = 4 : y = 4² - 2(4) - 19 = 16 - 8 - 19 = - 11 ⇒ (4, - 11)
the solutions are (- 6, 29), (4, - 11)